A Systematic Review of the Symptom Profile and Course of Methamphetamine-Associated Psychosis: Substance Use and Misuse. (21st March 2019) - Voce, Alexandra; Calabria, Bianca; Burns, Richard; Castle, David; McKetin, Rebecca
Abstract: Objectives : The psychiatric symptom profile of methamphetamine-associated psychosis (MAP) has varied considerably across studies of different research designs. We performed a systematic review to examine the available evidence for specific psychotic symptoms associated with MAP, including the clinical course and longitudinal changes in this symptom profile. Methods : Five key electronic databases were searched to identify studies that examined the symptom profile or clinical course of MAP in individuals identified as having MAP. The reporting of specific psychiatric symptoms, and duration of symptoms where available, was recorded for each study. Results : Ninety-four articles were identified ( n = 7387), including case-control ( k = 29), cross-sectional ( k = 20), experimental ( k = 6), case report ( k = 29), and longitudinal ( k = 20) studies. Persecutory delusions, auditory and visual auditory hallucinations were by far the most commonly reported symptoms (reported in 65–84% of studies). Hostility, conceptual disorganization, and depression were reported in a large proportion of studies (31–53%). Negative symptoms were mostly absent (<20%). The median percentage of participants with persistent psychotic symptoms (>1 month duration) across studies was 25% (excluding case reports). Conclusion : Persecutory delusions, auditory and visual hallucinations, hostility, depression and conceptual disorganization are central to MAP, whereas negative psychotic symptoms are typically absent. An overrepresentation of institutionalized or male participants may have overemphasized negative symptoms and underreported affective symptoms in past research. Symptoms of MAP may persist beyond one month after drug cessation in some individuals. Clinicians are encouraged to manage affective symptoms in MAP individuals, and monitor for the development of chronic psychotic symptoms.